Nature, knowledge and negation - Dahms, Harry F. (Bingley : Emerald Group Pub., 2009)
The first emphasis of the volume is on developments in the social theory of environmental issues, the environment, and the environmental crisis. The second emphasis is on the increasingly questionable possibility of shared knowledge at a time of increasing fragmentation of common frameworks, distraction from key issues, and dilution of the idea of objectivity. The thematic emphasis on environmental challenges and issues, includes one contribution on climate change, the resource crunch, and the global growth Imperative, along with critical responses by other experts in this field, and two contributions on the development of planetarian accountancy, and the ubiquity of risk in consumer societies. Further contributions address issues relating to the dialectic of selfhood, the aftermath of postmodernism, limitations inherent to feminist perspectives, the project of public sociology, the fortieth anniversary of Jurgen Habermas' classic, Knowledge and Human Interests, and the need for critical theory to rely on social research.
Includes bibliographical references.
Description based on print version record.
Keywords: Climatic changes -- Social aspects; Nature -- Social aspects; Conservation of the environment; Social theory; Social Science -- Sociology -- General